161k views
4 votes
Simplify with positive exponents... Show your work..

(3x^-2 y^5)^4

User Bogtan
by
6.4k points

2 Answers

6 votes
remember some basic rules

(ab)^c=(a^c)(b^c) and

(a^b)^c=a^(bc) and

x^(-m)= (1)/(x^m)
so


(3x^(-2)y^5)^4=((3x^(-2))^4)((y^5)^4)

(3x^(-2))^4=(3^4)((x^(-2)^4)=(81)(x^(-8))

(y^5)^4=y^(20)
we now have

81x^(-8)y^(20)

x^(-8)= (1)/(x^8) so

81x^(-8)y^(20)= (81y^(20))/(x^8)

User Rafael Soufraz
by
6.8k points
6 votes
(3x^-2 y^5)^4

= 81x^-8 y^20

=81y^20
------------
x^8
User Flo Bayer
by
6.1k points